High entropy disilicate nanoparticles / amorphous silicon dioxide@silicon carbide nanowire composite aerogel and preparation method and application thereof
Through the self-assembly and high-temperature calcination process of high-entropy disilicate nanoparticles and amorphous silica@silicon carbide nanowire composite aerogel, the problem of insufficient mechanical properties and high-temperature thermal insulation properties of high-entropy ceramic aerogels is solved. , realize effective thermal protection at high temperatures and expand the scope of application.
Patent Information
- Application Number
- CN202310625635.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-30
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-05-30
AI Technical Summary
The existing high-entropy ceramic aerogels have shortcomings in mechanical properties and high-temperature thermal insulation properties, and are difficult to effectively apply at high temperatures.
The composite aerogel of high entropy disilicate nanoparticles and amorphous silica@silicon carbide nanowires were prepared by self-assembly method, and the cross-linking and supercritical drying process were used for high-temperature calcination. It was formed with excellent results. Compound aerogel with mechanical properties and high temperature stability.
It realizes low room temperature thermal conductivity and high temperature stability, can keep the structure unchanged under an environment of 1200℃, and is suitable for high temperature thermal insulation and thermal protection, fills the research gap of high entropy ceramic composite aerogels, and expands high Application scope of entropy ceramics.
Smart Images

Figure CN116789442B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high entropy ceramic material preparation, and specifically relates to a high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel and a preparation method and application thereof. Background Art
[0002] Ceramic aerogels have attracted widespread attention in the field of lightweight structural materials such as thermal insulation, catalysis, and filtration due to their low density, high porosity, and large specific surface area. Traditional ceramic aerogels are usually assembled from oxide nanoparticles. Because they have abundant nanoscale pores, they can effectively inhibit the solid heat conduction and gas convection heat transfer of the material, and are a new type of thermal insulation material with excellent performance. However, since the nanoparticles are connected by sintering necks, the connection strength is too low, and aerogels generally have poor mechanical properties and are difficult to apply in practice. In addition, current aerogels generally have the problem of structural collapse at high temperatures, which causes the entire material to fail during service. (Reference "A review on the emerging resilient and multifunctional ceramic aerogels[J]" Journal of Materials Science & Technology, 2021, 75, 1-13.). Therefore, preparing a ceramic aerogel with excellent mechanical properties and high temperature stability, as well as good thermal insulation properties, is the best strategy to solve the current bottleneck in aerogel applications.
[0003] Silicon carbide nanowire aerogel is a spatial porous structure material composed of silicon carbide nanowires that are entangled and cross-linked. Due to its ultra-high porosity, low density, good mechanical properties, and excellent thermal and chemical stability, it has great application potential in the fields of thermal insulation and thermal protection. (Reference "Scalable Fabrication of Resilient SiC Nanowires Aerogels with Exceptional High-Temperature Stability[J]" ACS Applied Materials & Interfaces, 2019, 11(48), 45338-45344.) However, due to the large number of pores inside it (porosity>90%), and the difficulty in further regulating the pore size inside it, it is difficult to block the heat flow diffusion caused by thermal convection in the field of thermal insulation, and it is difficult to reflect its thermal protection function in the field of high-temperature thermal insulation (service temperature exceeds 200°C).
[0004] High-entropy ceramic aerogel is an emerging type of ceramic aerogel. Its skeleton is a highly porous structure formed by sintering and overlapping nanoparticles of high-entropy ceramics, and it usually has a large number of nanoscale pores inside. Due to the lattice distortion effect in high-entropy materials and the presence of nanopores, high-entropy ceramic aerogels generally have extremely low thermal conductivity. However, the high-entropy ceramic aerogels synthesized so far are mostly powders with poor mechanical properties, which severely limits their scope of application. Recently, some studies have used high-entropy aerogel powder for secondary molding and sintering to prepare aerogel blocks. Although this method solves the problem of poor mechanical properties, the porosity of the synthesized high-entropy ceramic blocks is very low, which cannot meet the definition of high porosity and high specific surface area of aerogels. In addition, the thermal conductivity of the material will also increase significantly with the densification of the ceramic blocks, and efficient thermal protection cannot be achieved. (Reference "A novel high-entropy (Sm 0.2 Eu 0.2 Tb 0.2 Dy 0.2 Lu 0.2 ) 2 Zr 2 O 7 ceramic aerogel with ultralow thermal conductivity[J]" Ceramics International, 2021, 47(21), 29960-29968.) Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel and its preparation method and application, so as to solve the technical problems that the current silicon carbide nanowire aerogel is difficult to shape, has poor mechanical properties, and has insufficient high-temperature thermal insulation performance.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The present invention discloses a high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel, wherein the composite aerogel is prepared by self-assembly of high entropy disilicate nanoparticle aerogel and silicon carbide nanowires wrapped by amorphous silicon dioxide; wherein:
[0008] The chemical formula of the high entropy disilicate nanoparticle aerogel is (Y 0.2 Yb 0.2 Er 0.2 Tm 0.2 G 0.2 ) 2 Si 2 O 7The particle size is 20-100 nm, the crystal structure is monoclinic, and each Si atom is composed of four O atoms [SiO 4 ] tetrahedron, two [SiO 4 ]tetrahedrons are connected by sharing vertices to form [SiO 7 ] structural unit, each rare earth atom and six O atoms form an octahedron, [SiO 7 ] structural units are linked together;
[0009] The amorphous silicon dioxide@silicon carbide nanowire aerogel is formed by silicon carbide nanowires wrapped in amorphous silicon dioxide and entangled with each other, and has a diameter of 50 to 300 nm and a density of 100 to 150 mg / cm 3 .
[0010] Preferably, the density of the composite aerogel is 100 to 300 mg / cm 3 .
[0011] Preferably, the room temperature thermal conductivity of the composite aerogel is as low as 0.07 W / m·K, and no phase change and segregation occur after heat treatment at 1200° C. in air atmosphere for 5 h.
[0012] Preferably, the composite aerogel is treated at 600°C on the hot side for 1200s, and the back side temperature is only 200°C.
[0013] The present invention also discloses a method for preparing the high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel, comprising the following steps:
[0014] 1) Mix five kinds of RECl in equal molar ratios 3 or RE(NO 3 ) 3 Dissolved in anhydrous ethanol, then added with an ethanol solution of tetraethyl orthosilicate to obtain a mixed solution; wherein RE = Y, Yb, Er, Tm, and Gd;
[0015] 2) placing the amorphous silicon dioxide@silicon carbide nanowire aerogel in the mixed solution obtained in step 1) and fully immersing it, then adding a proton scavenger, stirring evenly, standing and cross-linking, and obtaining a composite gel;
[0016] 3) aging the obtained composite gel for 6 to 10 days, washing the gel with anhydrous ethanol once every 24 hours, at least 3 times, and then performing supercritical drying to obtain a composite xerogel;
[0017] 4) The composite dry gel is placed in an air atmosphere and calcined to obtain a high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel. The chemical formula of the composite aerogel is (Y 0.2 Yb 0.2Er 0.2 Tm 0.2 G 0.2 ) 2 Si 2 O 7 NP / amorphous SiO 2 @SiC NWA.
[0018] Preferably, in step 1), the amount of tetraethyl orthosilicate is about the same as the amount of RECl used. 3 or RE(NO 3 ) 3 The ratio of the total amount of substance is (1~1.1):1.
[0019] Preferably, in step 2), the proton scavenger is propylene oxide, and the ratio of the amount of propylene oxide to the total amount of ions in the solution is (0.5-2):1.
[0020] Preferably, in step 3), the supercritical temperature is 32-38° C. and the pressure is 73-80 atm.
[0021] Preferably, in step 4), the calcination temperature is 400-1000° C., the holding time is 3 hours, and the temperature is increased from room temperature to the calcination temperature at a heating rate of 1-10° C. / min.
[0022] The present invention also discloses the use of the high entropy disilicate nanoparticles / amorphous silicon dioxide@silicon carbide nanowire composite aerogel in the preparation of high temperature resistant heat insulation materials.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel disclosed in the present invention is expressed as (Y 0.2 Yb 0.2 Er 0.2 Tm 0.2 G 0.2 ) 2 Si 2 O 7 NP / amorphous SiO 2@SiC NWA is synthesized by self-assembly of high entropy ceramic nanoparticle aerogel and amorphous silicon dioxide @silicon carbide nanowire composite aerogel. The room temperature thermal conductivity of the composite aerogel is as low as 0.07W / m·K. The hot surface is treated at 600℃ for 1200s, and the back temperature is only 200℃. It basically does not deform under the pressure of 200g weight, and has excellent thermal insulation performance and excellent mechanical properties. In addition, the composite aerogel has excellent high-temperature stability and can be heat treated at 1200℃ in air atmosphere for 5h without phase change or segregation. The composite aerogel is suitable for use in high-temperature thermal insulation and high-efficiency thermal protection. It fills the research gap of high-entropy ceramic composite aerogels, enriches the high-entropy material system, and expands the application range of high-entropy ceramics.
[0025] The present invention also discloses a method for preparing the above-mentioned high entropy disilicate nanoparticles / amorphous silicon dioxide @ silicon carbide nanowire composite aerogel, wherein the amorphous silicon dioxide @ silicon carbide nanowire aerogel is fully soaked in a high entropy precursor solution, and then the gel is synthesized by a proton scavenger crosslinking method, and a composite dry gel is obtained by supercritical drying, and finally a high entropy disilicate nanoparticles / amorphous silicon dioxide @ silicon carbide nanowire composite aerogel is successfully synthesized by a high-temperature pyrolysis and roasting method. The method has the advantages of simple process, economic and pollution-free, suitable for large-scale production, and wide application range. Compared with other methods for preparing high entropy ceramic aerogels, the high entropy disilicate nanoparticles / amorphous silicon dioxide @ silicon carbide nanowire composite aerogel synthesized by this method has excellent mechanical properties, high temperature stability and excellent thermal insulation properties, and can provide effective thermal protection under high temperature conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a process flow chart for preparing a high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel of the present invention;
[0027] Figure 2 This is a macroscopic morphology photograph of the high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel prepared in Example 1;
[0028] Figure 3 The microscopic morphology of the high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel prepared in Example 2; wherein (a) is a photo of the composite aerogel magnified 4000 times; (b) is a photo of the composite aerogel magnified 120,000 times;
[0029] Figure 4 This is a macroscopic photograph of the high entropy disilicate nanoparticles / amorphous silicon dioxide@silicon carbide nanowire composite aerogel prepared in Example 2 under a 200 g weight pressure;
[0030] Figure 5 This is the XRD pattern of the high entropy disilicate nanoparticles / amorphous silicon dioxide@silicon carbide nanowire composite aerogel prepared in Example 3;
[0031] Figure 6 This is a comparison diagram of XRD of the high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel prepared in Example 3 before and after heat treatment;
[0032] Figure 7 This is a quality comparison diagram of the high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel prepared in Example 4 before and after heat treatment;
[0033] Figure 8 This is the thermal conductivity diagram of the high entropy disilicate nanoparticles / amorphous silicon dioxide@silicon carbide nanowire composite aerogel prepared in Example 5.
[0034] Fig. 9 This is a temperature change diagram of the back side of the high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel prepared in Example 6 after being treated at a hot surface of 600°C for 1200s. DETAILED DESCRIPTION
[0035] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0036] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0037] The present invention is further described in detail below in conjunction with the accompanying drawings:
[0038] See also Figure 1, combined with the process flow chart, a high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel of the present invention is described, comprising the following steps:
[0039] 1) Mix five kinds of RECl in equal molar ratios 3 or RE(NO 3 ) 3 Dissolve in anhydrous ethanol, and add tetraethyl orthosilicate ethanol solution drop by drop to obtain a mixed solution; wherein RE = Y, Yb, Er, Tm, and Gd. The amount of tetraethyl orthosilicate is equal to the amount of RECl used. 3 or RE(NO 3 ) 3 The ratio of the total amount of substance is (1~1.1):1.
[0040] 2) The prefabricated amorphous silicon dioxide@silicon carbide nanowire aerogel is placed in the mixed solution prepared in step 1) and fully immersed, and the density of the silicon carbide nanowire is 100-150 mg / cm 3 ; Then, a proton scavenger propylene oxide is added dropwise to the solution, slowly stirred, and then allowed to stand for cross-linking to obtain a composite gel; wherein the ratio of the amount of propylene oxide to the total amount of ions in the solution is (0.5-2):1.
[0041] 3) fully aging the composite gel obtained in step 2), washing the gel, and then performing supercritical drying to obtain a composite dry gel; wherein the aging time is 6 to 10 days, the washing is to wash the gel once every 24 hours with anhydrous ethanol, at least 3 times, the supercritical temperature is 32 to 38° C., and the pressure is 73 to 80 atm.
[0042] 4) calcining the composite dry gel obtained in step 3) in an air atmosphere to obtain a high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel, wherein the calcination temperature is 400-1000°C, the holding time is 3 hours, and the heating rate is 1-10°C / min.
[0043] The prefabricated amorphous silicon dioxide@silicon carbide nanowire aerogel described in step 2) is prepared according to the method disclosed in the invention patent No. 201811626203.6, which specifically includes the following steps:
[0044] 1) using siloxane as a raw material, anhydrous ethanol as a solvent, and water as a cross-linking agent to prepare a polysiloxane sol;
[0045] 2) using carbon felt as the basic unit constituting the template skeleton and fully impregnating it with polysiloxane sol;
[0046] 3) heating the three-dimensional porous carbon fiber skeleton to the curing temperature of the polysiloxane sol, and keeping the temperature until the polysiloxane gel / porous carbon fiber skeleton is formed;
[0047] 4) In an argon atmosphere, the polysiloxane gel / porous carbon fiber skeleton was heated to 1550° C. and kept warm for 3 h to obtain a silicon carbide nanowire / carbon fiber composite structure;
[0048] 5) The silicon carbide nanowire / carbon fiber composite structure is heated to 800° C. in air and kept warm for 3 h to obtain an amorphous silicon dioxide@silicon carbide nanowire aerogel.
[0049] Example 1
[0050] In this embodiment, a high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel is prepared under the conditions that the ratio of the amount of tetraethyl orthosilicate to the total amount of ions in the solution is 1:1, the ratio of the amount of propylene oxide to the total amount of ions in the solution is 0.75:1, the calcination temperature is 500°C, the calcination time is 3h, and the heating rate is 5°C / min. The specific steps are as follows:
[0051] Step 1: Mix five RECl in equal molar ratios. 3 or RE(NO 3 ) 3 Dissolve in anhydrous ethanol, and add tetraethyl orthosilicate ethanol solution drop by drop to obtain a mixed solution; wherein RE = Y, Yb, Er, Tm, and Gd. The amount of tetraethyl orthosilicate is equal to the amount of RECl used. 3 or RE(NO 3 ) 3 The ratio of the amount of total substance is 1:1;
[0052] Step 2: Place the prefabricated amorphous silicon dioxide@silicon carbide nanowire aerogel in the mixed solution for full immersion. The density of the silicon carbide nanowire is 100 mg / cm 3 ; Then, a proton scavenger propylene oxide is added dropwise to the solution, slowly stirred, and then allowed to stand for crosslinking to obtain a composite gel; wherein the ratio of the amount of propylene oxide to the total amount of ions in the solution is equal to 0.75:1;
[0053] Step 3: fully age the obtained composite gel, wash the gel, and then perform supercritical drying to obtain a composite xerogel; wherein the aging time is 6 to 10 days, and the gel is washed with anhydrous ethanol once every 24 hours, at least 3 times, the supercritical temperature is 32 to 38°C, and the pressure is 73 to 80 atm;
[0054] Step 4: calcining the composite dry gel in an air atmosphere to obtain a high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel, wherein the calcination temperature is 500°C, the holding time is 3h, and the heating rate is 5°C / min.
[0055] Figure 2 This is a macroscopic photograph of the high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel prepared in this example. The sample is in the shape of a gray round block with low density and high porosity.
[0056] Example 2
[0057] In this embodiment, a high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel is prepared under the conditions that the ratio of the amount of tetraethyl orthosilicate to the total amount of ions in the solution is equal to 1:1, the ratio of the amount of propylene oxide to the total amount of ions in the solution is equal to 1:1, the calcination temperature is 500°C, the calcination time is 3h, and the heating rate is 5°C / min. The specific steps are as follows:
[0058] Step 1: Mix five RECl in equal molar ratios. 3 or RE(NO 3 ) 3 Dissolve in anhydrous ethanol, and add tetraethyl orthosilicate ethanol solution drop by drop to obtain a mixed solution; wherein RE = Y, Yb, Er, Tm, and Gd. The amount of tetraethyl orthosilicate is equal to the amount of RECl used. 3 or RE(NO 3 ) 3 The ratio of the amount of total substance is 1:1;
[0059] Step 2: Place the prefabricated amorphous silicon dioxide@silicon carbide nanowire aerogel in the mixed solution for full immersion. The density of the silicon carbide nanowire is 100 mg / cm 3 ; Then, a proton scavenger propylene oxide is added dropwise to the solution, slowly stirred, and then allowed to stand for cross-linking to obtain a composite gel; wherein the ratio of the amount of propylene oxide to the total amount of ions in the solution is equal to 1:1;
[0060] Step 3: fully age the obtained composite gel, wash the gel, and then perform supercritical drying to obtain a composite xerogel; wherein the aging time is 6 to 10 days, and the gel is washed with anhydrous ethanol once every 24 hours, at least 3 times, the supercritical temperature is 32 to 38°C, and the pressure is 73 to 80 atm;
[0061] Step 4: calcining the composite dry gel in an air atmosphere to obtain a high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel, wherein the calcination temperature is 500°C, the holding time is 3h, and the heating rate is 5°C / min.
[0062] Figure 3 This is a scanning photo of the high entropy disilicate nanoparticles / amorphous silicon dioxide@silicon carbide nanowire composite aerogel prepared in this embodiment. It can be seen from the figure that the particle size of the high entropy ceramic aerogel particles is about 30nm, the diameter of the silicon carbide nanowires is 50-300nm, and the high entropy ceramic particles and silicon carbide nanowires are well combined.
[0063] Figure 4 This is a macroscopic photograph of the high entropy disilicate nanoparticles / amorphous silicon dioxide@silicon carbide nanowire composite aerogel prepared in Example 2 under a 200g weight pressure. It can be seen that the sample structure is not destroyed under the weight pressure and basically no deformation occurs, indicating that the composite aerogel has excellent mechanical properties.
[0064] Example 3
[0065] In this embodiment, a high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel is prepared under the conditions that the ratio of the amount of tetraethyl orthosilicate to the total amount of ions in the solution is equal to 1.1:1, the ratio of the amount of propylene oxide to the total amount of ions in the solution is equal to 1:1, the calcination temperature is 1000°C, the calcination time is 3h, and the heating rate is 10°C / min. The specific steps are as follows:
[0066] Step 1: Mix five RECl in equal molar ratios. 3 or RE(NO 3 ) 3 Dissolve in anhydrous ethanol, and add tetraethyl orthosilicate ethanol solution drop by drop to obtain a mixed solution; wherein RE = Y, Yb, Er, Tm, and Gd. The amount of tetraethyl orthosilicate is equal to the amount of RECl used. 3 or RE(NO 3 ) 3 The ratio of the amount of total substance is 1.1:1;
[0067] Step 2: Place the prefabricated amorphous silicon dioxide@silicon carbide nanowire aerogel in the mixed solution for full immersion. The density of the silicon carbide nanowire is 100 mg / cm 3 ; Then, a proton scavenger propylene oxide is added dropwise to the solution, slowly stirred, and then allowed to stand for cross-linking to obtain a composite gel; wherein the ratio of the amount of propylene oxide to the total amount of ions in the solution is equal to 1:1;
[0068] Step 3: fully age the obtained composite gel, wash the gel, and then perform supercritical drying to obtain a composite xerogel; wherein the aging time is 6 to 10 days, and the gel is washed with anhydrous ethanol once every 24 hours, at least 3 times, the supercritical temperature is 32 to 38°C, and the pressure is 73 to 80 atm;
[0069] Step 4: calcining the composite dry gel in an air atmosphere to obtain a high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel, wherein the calcination temperature is 1000°C, the holding time is 3h, and the heating rate is 10°C / min.
[0070] Figure 5 This is the XRD spectrum of the high entropy disilicate nanoparticles / amorphous silica @ silicon carbide nanowire composite aerogel prepared in this embodiment. It can be seen from the figure that the 2θ of the high entropy oxide ceramic powder has multiple diffraction peaks representing high entropy disilicate and silicon carbide phases between 10° and 90°, and no obvious diffraction peaks are seen at other positions, indicating that the high entropy disilicate particles are successfully combined with the amorphous silica @ silicon carbide nanowires, and the material is relatively pure.
[0071] Figure 6 This is the XRD comparison diagram of the high entropy disilicate nanoparticles / amorphous silicon dioxide@silicon carbide nanowire composite aerogel prepared in this example before and after heat treatment. The heat treatment temperature is 1200°C and the holding time is 5h. It can be seen that the sample did not undergo phase change or segregation after heat treatment.
[0072] Example 4
[0073] In this embodiment, a high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel is prepared under the conditions that the ratio of the amount of tetraethyl orthosilicate to the total amount of ions in the solution is equal to 1:1, the ratio of the amount of propylene oxide to the total amount of ions in the solution is equal to 1:1, the calcination temperature is 1000°C, the calcination time is 3h, and the heating rate is 10°C / min. The specific steps are as follows:
[0074] Step 1: Mix five RECl in equal molar ratios. 3 or RE(NO 3 ) 3 Dissolve in anhydrous ethanol, and add tetraethyl orthosilicate ethanol solution drop by drop to obtain a mixed solution; wherein RE = Y, Yb, Er, Tm, and Gd. The amount of tetraethyl orthosilicate is equal to the amount of RECl used. 3 or RE(NO 3 ) 3 The ratio of the amount of total substance is 1:1;
[0075] Step 2: Place the prefabricated amorphous silicon dioxide@silicon carbide nanowire aerogel in the mixed solution for full immersion. The density of the silicon carbide nanowire is 100 mg / cm 3 ; Then, a proton scavenger propylene oxide is added dropwise to the solution, slowly stirred, and then allowed to stand for cross-linking to obtain a composite gel; wherein the ratio of the amount of propylene oxide to the total amount of ions in the solution is equal to 1:1;
[0076] Step 3: fully age the obtained composite gel, wash the gel, and then perform supercritical drying to obtain a composite xerogel; wherein the aging time is 6 to 10 days, and the gel is washed with anhydrous ethanol once every 24 hours, at least 3 times, the supercritical temperature is 32 to 38°C, and the pressure is 73 to 80 atm;
[0077] Step 4: calcining the composite dry gel in an air atmosphere to obtain a high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel, wherein the calcination temperature is 1000°C, the holding time is 3h, and the heating rate is 10°C / min.
[0078] Figure 7 This is a comparison chart of the mass of the high entropy disilicate nanoparticles / amorphous silicon dioxide@silicon carbide nanowire composite aerogel prepared in this embodiment after heat treatment. The heat treatment temperature is 1200°C, the heating rate is 10°C / min, and the atmosphere is air. It can be seen from the figure that the mass change of the composite aerogel does not exceed 0.5%, indicating that the composite aerogel has good high temperature stability.
[0079] Example 5
[0080] In this embodiment, a high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel is prepared under the conditions that the ratio of the amount of tetraethyl orthosilicate to the total amount of ions in the solution is equal to 1:1, the ratio of the amount of propylene oxide to the total amount of ions in the solution is equal to 1:1, the calcination temperature is 400°C, the calcination time is 3h, and the heating rate is 5°C / min. The specific steps are as follows:
[0081] Step 1: Mix five RECl in equal molar ratios. 3 or RE(NO 3 ) 3 Dissolve in anhydrous ethanol, and add tetraethyl orthosilicate ethanol solution drop by drop to obtain a mixed solution; wherein RE = Y, Yb, Er, Tm, and Gd. The amount of tetraethyl orthosilicate is equal to the amount of RECl used. 3 or RE(NO 3 ) 3 The ratio of the amount of total substance is 1:1;
[0082] Step 2: Place the prefabricated amorphous silicon dioxide@silicon carbide nanowire aerogel in the mixed solution for full immersion. The density of the silicon carbide nanowire is 100 mg / cm 3 ; Then, a proton scavenger propylene oxide is added dropwise to the solution, slowly stirred, and then allowed to stand for cross-linking to obtain a composite gel; wherein the ratio of the amount of propylene oxide to the total amount of ions in the solution is equal to 1:1;
[0083] Step 3: fully age the obtained composite gel, wash the gel, and then perform supercritical drying to obtain a composite xerogel; wherein the aging time is 6 to 10 days, and the gel is washed with anhydrous ethanol once every 24 hours, at least 3 times, the supercritical temperature is 32 to 38°C, and the pressure is 73 to 80 atm;
[0084] Step 4: calcining the composite dry gel in an air atmosphere to obtain a high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel, wherein the calcination temperature is 400°C, the holding time is 3h, and the heating rate is 5°C / min.
[0085] Figure 8 This is a thermal conductivity diagram of the high entropy disilicate nanoparticles / amorphous silica@silicon carbide nanowire composite aerogel prepared in this embodiment and the original amorphous silica@silicon carbide nanowire. It can be seen from the figure that due to the incorporation of high entropy ceramic particles into the nanowires, the thermal conductivity has increased slightly, but is still relatively low.
[0086] Example 6
[0087] In this embodiment, a high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel is prepared under the conditions that the ratio of the amount of tetraethyl orthosilicate to the total amount of ions in the solution is equal to 1:1, the ratio of the amount of propylene oxide to the total amount of ions in the solution is equal to 1:1, the calcination temperature is 500°C, the calcination time is 3h, and the heating rate is 5°C / min. The specific steps are as follows:
[0088] Step 1: Mix five RECl in equal molar ratios. 3 or RE(NO 3 ) 3 Dissolve in anhydrous ethanol, and add tetraethyl orthosilicate ethanol solution drop by drop to obtain a mixed solution; wherein RE = Y, Yb, Er, Tm, and Gd. The amount of tetraethyl orthosilicate is equal to the amount of RECl used. 3 or RE(NO 3 ) 3 The ratio of the amount of total substance is 1:1;
[0089] Step 2: Place the prefabricated amorphous silicon dioxide@silicon carbide nanowire aerogel in the mixed solution for full immersion. The density of the silicon carbide nanowires is 150 mg / cm 3 ; Then, a proton scavenger propylene oxide is added dropwise to the solution, slowly stirred, and then allowed to stand for cross-linking to obtain a composite gel; wherein the ratio of the amount of propylene oxide to the total amount of ions in the solution is equal to 1:1;
[0090] Step 3: fully age the obtained composite gel, wash the gel, and then perform supercritical drying to obtain a composite xerogel; wherein the aging time is 6 to 10 days, and the gel is washed with anhydrous ethanol once every 24 hours, at least 3 times, the supercritical temperature is 32 to 38°C, and the pressure is 73 to 80 atm;
[0091] Step 4: calcining the composite dry gel in an air atmosphere to obtain a high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel, wherein the calcination temperature is 500°C, the holding time is 3h, and the heating rate is 5°C / min.
[0092] Fig. 9 The temperature change diagram of the back side of the high entropy disilicate nanoparticles / amorphous silicon dioxide@silicon carbide nanowire composite aerogel prepared in this example after being treated at 600°C for 1200s. Fig. 9 It can be seen that the temperature on the back of the sample is basically stable at around 200°C, indicating that the composite aerogel has good thermal insulation properties.
[0093] In summary, the expression of a high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel disclosed in the present invention is (Y 0.2 Yb 0.2 Er 0.2 Tm 0.2 G 0.2 ) 2 Si 2 O 7 NP / amorphous SiO 2 @SiC NWA. This method is simple, economical, pollution-free, and suitable for large-scale production. The high-entropy disilicate nanoparticle / amorphous silicon dioxide @ silicon carbide nanowire composite aerogel has excellent mechanical properties, thermal insulation properties, and excellent high-temperature stability. It can be heat-treated at 1200°C in air atmosphere for 5 hours without phase change or segregation. The composite aerogel is suitable for use in high-temperature thermal insulation and high-efficiency thermal protection. This series of high-entropy oxides fills the research gap of high-entropy ceramic composite aerogels and expands the application range of high-entropy ceramics.
[0094] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel, characterized in that: The composite aerogel is made of high entropy disilicate nanoparticle aerogel and silicon carbide nanowires wrapped in amorphous silicon dioxide by self-assembly; wherein: The chemical formula of the high entropy disilicate nanoparticle aerogel is (Y 0.2 Yb 0.2 Er 0.2 Tm 0.2 G 0.2 )2Si2O7, particle size is 20~100 nm, crystal structure is monoclinic, each Si atom and four O atoms form [SiO4] tetrahedron, two [SiO4] tetrahedrons are connected by sharing vertices to form [SiO7] structural unit, each rare earth atom and six O atoms form octahedron, connecting [SiO7] structural units together; The amorphous silicon dioxide@silicon carbide nanowire aerogel is formed by the intertwining of silicon carbide nanowires wrapped in amorphous silicon dioxide, with a diameter of 50-300 nm and a density of 100-150 mg / cm 3 ; The room temperature thermal conductivity of the composite aerogel is as low as 0.07 W / m·K, and no phase change or segregation occurs when heat-treated at 1200 ℃ in air atmosphere for 5 h. The composite aerogel is treated at 600 ℃ on the hot surface for 1200 s, and the back surface temperature is only 200 ℃.
2. The high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel according to claim 1, characterized in that: The density of the composite aerogel is 100~300 mg / cm 3 .
3. The method for preparing the high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel according to any one of claims 1 to 2, characterized in that: The following steps are involved: 1) Dissolve five kinds of RECl3 or RE(NO3)3 in anhydrous ethanol in equal molar ratios, and then add an ethanol solution of tetraethyl orthosilicate to obtain a mixed solution; wherein RE = Y, Yb, Er, Tm, and Gd; 2) fully immersing the amorphous silicon dioxide@silicon carbide nanowire aerogel in the mixed solution prepared in step 1), then adding a proton scavenger, stirring evenly, standing and cross-linking to obtain a composite gel; 3) aging the obtained composite gel for 6 to 10 days, and washing the gel with anhydrous ethanol once every 24 hours, at least 3 times, and then performing supercritical drying to obtain a composite xerogel; the supercritical temperature is 32 to 38°C and the pressure is 73 to 80 atm; 4) The composite dry gel is calcined in an air atmosphere to obtain a high entropy disilicate nanoparticle / amorphous silicon dioxide@silicon carbide nanowire composite aerogel. The chemical formula of the composite aerogel is (Y 0.2 Yb 0.2 Er 0.2 Tm 0.2 G 0.2 )2Si2O7 NP / amorphous SiO2@SiC NWA; The calcination temperature is 400~1000℃, the holding time is 3h, and the temperature is increased from room temperature to the calcination temperature at a heating rate of 1~10℃ / min.
4. The method for preparing high entropy disilicate nanoparticles / amorphous silicon dioxide@silicon carbide nanowire composite aerogel according to claim 3, characterized in that: In step 1), the ratio of the amount of tetraethyl orthosilicate to the total amount of RECl3 or RE(NO3)3 used is (1~1.1):
1.
5. The method for preparing high entropy disilicate nanoparticles / amorphous silicon dioxide@silicon carbide nanowire composite aerogel according to claim 3, characterized in that: In step 2), propylene oxide is used as a proton scavenger, and the ratio of the amount of propylene oxide to the total amount of ions in the solution is (0.5~2):
1.
6. Use of the high entropy disilicate nanoparticles / amorphous silicon dioxide@silicon carbide nanowire composite aerogel according to any one of claims 1 to 2 in the preparation of high temperature resistant thermal insulation materials.
